Circulating tumor DNA analysis in breast cancer: Is it ready for prime-time?. (February 2019) - Buono, Giuseppe; Gerratana, Lorenzo; Bulfoni, Michela; Provinciali, Nicoletta; Basile, Debora; Giuliano, Mario; Corvaja, Carla; Arpino, Grazia; Del Mastro, Lucia; De Placido, Sabino; De Laurentiis, Michele; Cristofanilli, Massimo; et al.
Highlights: Although informative cfDNA is not cancer specific. A priori PCR techniques and Genome sequencing have different clinical implications. Longitudinal ctDNA assessments can track both tumor burden and actionable mutations. Abstract: Precision Medicine is becoming the new paradigm in healthcare as it enables better resources allocation, treatment optimization with a potential side-effects reduction and consequent impact on quality of life and survival. This revolution is being catalyzed by liquid biopsy technologies, which provide prognostic and predictive information for advanced cancer patients, without the analytical and procedural drawbacks of tissue-biopsy. In particular, circulating tumor DNA (ctDNA) is gaining momentum as a clinically feasible option capable to capture both spatial and temporal tumor heterogeneity. Several techniques are currently available for ctDNA extraction and analysis, each with its preferential case scenarios and preanalytical implications which must be taken into consideration to effectively support clinical decision-making and to better highlight its clinical utility. Aim of this review is to summarize both analytical developments and clinical evidences to offer a comprehensive update on the deployment of ctDNA in breast cancer's (BC) characterization and treatment.